PENERAPAN P5 DIMENSI BERKEBINEKAAN GLOBAL DALAM MENANANAMKAN NILAI BUDAYA LOKAL DI SEKOLAH DASAR - Kristiana Darmayana; Siprianus Jewarut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of the P5 Program on the global diversity dimension in instilling local cultural values in class V of SDS Amkur Bengkayang. The study used a qualitative approach with observation, interview, and documentation methods. The subjects of the study were class V students and homeroom teachers. The results of the study indicate that the P5 program has helped students understand and implement local cultural values such as the 5S culture (Smile, Greet, Greet, Polite, and Courteous) and mutual cooperation. However, several challenges are still faced, such as the low spirit of mutual cooperation and the use of impolite language. Through the implementation of P5, local culture can be instilled more effectively, although innovation in learning strategies is needed to increase student participation.